Case Report and Theoretical Description of Accelerated Resolution Therapy (ART) for Military-Related Post-Traumatic Stress Disorder. Issue 1 (1st January 2014) - Kip, Kevin E.; Shuman, Amy; Hernandez, Diego F.; Diamond, David M.; Rosenzweig, Laney
ABSTRACT: Objectives: This article describes a new, brief exposure-based psychotherapy known as Accelerated Resolution Therapy (ART) that is currently being evaluated as a treatment for combat-related post-traumatic stress disorder (PTSD). Methods: We describe a case report of an Army veteran with combat-related PTSD who was treated with 2 sessions of ART and experienced significant clinical improvement. We then discuss the theoretical basis and major components of the ART protocol, including use of lateral left–right eye movements, and differentiate ART with evidence-based psychotherapies currently endorsed by the Department of Defense and Veterans Administration. Results: The number of military personnel who have served in the wars in Iraq and Afghanistan and are afflicted with PTSD is likely in the hundreds of thousands. The ART protocol, which is delivered in 2 to 5 sessions and without homework, uses the psychotherapeutic practices of imaginal exposure and imagery rescripting (IR) facilitated through sets of eye movements. In addition to its brevity, a novel component of ART is use of IR to "replace" negative imagery (and other sensations) with positive imagery. Conclusions: This theoretical description of ART and single case report provide a rationale for future formal evaluation of ART for treatment of military-related PTSD.